2015
DOI: 10.1016/j.chb.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept clarity, social support, and compulsive Internet use: A study of the US and the UAE

Abstract: Compulsive Internet Use (CIU) has been mostly studied among adolescents, yet some studies reveal that this can be a problem for the adult population, too. The lack of agreement on diagnostic tools and cut-off points results in markedly different prevalence figures. Building on Charlton's (2002) distinction between core CIU and positive engagement dimensions, the first objective was to confirm that prevalence figures including the core dimensions of CIU were lower than those including the engagement dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 56 publications
(97 reference statements)
0
27
0
1
Order By: Relevance
“…To the authors' knowledge, the relationship between self-concept clarity and IGD has not been studied yet, but several researches have revealed a significant correlation between the self-concept clarity and Internet addiction (Israelashvili et al, 2012;Matsuba, 2006;Quinones & Kakabadse 2015a;Quinones & Kakabadse 2015b). According to the findings of this research, players' self-concept clarity was significantly related to IGD and it was a significant predictor of IGD.…”
Section: Discussionmentioning
confidence: 52%
“…To the authors' knowledge, the relationship between self-concept clarity and IGD has not been studied yet, but several researches have revealed a significant correlation between the self-concept clarity and Internet addiction (Israelashvili et al, 2012;Matsuba, 2006;Quinones & Kakabadse 2015a;Quinones & Kakabadse 2015b). According to the findings of this research, players' self-concept clarity was significantly related to IGD and it was a significant predictor of IGD.…”
Section: Discussionmentioning
confidence: 52%
“…Elhai et al (2017) find that smartphone addiction involves two mechanisms-the craving for positive mood and the desire to alleviate negative mood. The hedonic management model of addiction is used to explain a wide spectrum of behavioural addictions intimately involved with hedonic management, such as gambling addiction (Brown, 1993), crime addiction (Brown, 1997), exercise addiction (Kerr, Lindner, & Blaydon, 2008), computer addiction (Charlton, 2002), Internet addiction (Quinones & Kakabadse, 2015) and online gaming addiction (Clark, 2006;Hussain & Griffiths, 2014).…”
Section: The Hedonic Management Model Of Addictionmentioning
confidence: 99%
“…Research has shown, for example, that SCC correlates positively with conscientiousness (Campbell et al, 1996;Fite et al, 2017) and negatively with impulsivity (Campbell et al, 1996;Ellison & Levy, 2012;Matto & Realo, 2001). SCC also negatively predicts compulsive internet use (Israelashvili, Kim, and Bukobza, 2012;Quinones & Kakabadse, 2015) and relates negatively to maladaptive coping behaviors such as procrastination (Petrie, 2014), denial, behavioral disengagement, and emotional disengagement (Smith, Wethington, & Zhan, 1996). In addition, SCC relates negatively to emotion dysregulation variables, including negative affect (Bond, Ruaro, & Wingrove, 2006;Campbell et al, 1996;Lear & Pepper 2016;Lee-Flynn, Pomaki, DeLongis, Biesanz, & Puterman, 2011;Nezlek & Plesko, 2001;Scala et al, 2018), depression (Bobrowski, DeMarree, Lodi-Smith, & Naragon-Gainmey, 2018;Campbell et al, 1996;Chang, 2001;Lee-Flynn et al, 2011), and feelings of tenseness, boredom, and dejection in the context of goal pursuit (Kernis, Paradise, Whitaker, Wheatman, & Goldman, 2000).…”
Section: Introductionmentioning
confidence: 99%